RANCANG BANGUN SISTEM INFORMASI PEMBELIAN OBAT PADA KLINIK DJANTI MEDIKA BEKASI - Rian, Hesti; Nugroho, Tri Putro (POLITEKNIK LP3I JAKARTA, 2019)
Information systems are needed in the process of getting accurate data in an activity in an organization or business field. Such as drug purchase activities at the Djanti Medika Clinic which require accurate data that is appropriate in connection with data on the number of drugs to be ordered and received from the distributor. This research was conducted to create a design for purchasing information systems that are expected to help and facilitate in providing accurate data on purchasing activities carried out at the Djanti Medika Clinic with system design using the Unified Modeling Language (UML) and the PHP programming language.Key words: information systems, create a design, purchase